VD_FINDINFO AI 82/17 - 357/2019 vom 12. November 2019 - VD Tribunal cantonal (2019)
RENTE D'INVALIDITÉ, ATTEINTE À LA SANTÉ PHYSIQUE, ATTEINTE À LA SANTÉ PSYCHIQUE | 28 LAI, 4 LAI, 6 LPGA, 7 LPGA, 8 LPGA